The role of supervisory mechanisms in improving financial reporting quality by Vietnam public non-business unit - Quoc Thuan Pham; Thi Hanh Dung Truong; Xuan Thuy Ho; Quoc Thinh Nguyen (Cogent Business & Management, 2022)
Based primarily on agency theory, this study aims to examine the role of internal and external supervisory mechanisms in improving financial reporting quality by public non-business units in Vietnam. Quantitative research with a survey method was carried out on a sample of 362 public non-business units in Ha Noi, Da Nang, and Ho Chi Minh City, Vietnam. The data collection period spread from March to May 2021. The research hypotheses were tested by PLS-SEM. The research results show that all three factors independent audit, internal control effectiveness, and financial inspection frequency had positive impacts on the financial reporting quality; internal control effectiveness has a mediating role in the relationship between independent audit, financial inspection frequency, and financial reporting quality. This study is the first to examine the chain from independent audit, financial inspection frequency, internal control effectiveness, and financial reporting quality in the context of public non-business units in an emerging economy. Furthermore, the study is the basis for setting policies and regulations to improve financial reporting quality in public non-business units.
Keywords: 650; financial inspection frequency; financial reporting quality; Independent audit; internal control effectiveness; public non-business units; supervisory mechanisms